Intention In Switching To Electronic Money In Millennial Generation - Ricky Angga Ariska (UMSurabaya Publishing, 2020)
This research is talk about switching from conventional money to electronic money in millennials generation. Sampling technique used in this research is purposive sampling. Respondent criteria are individual that have electronic money account and have done transactions three times using electronic money. The research sample used was 100 respondents. The analysis technique used in this research is validity test, reliability test, multiple regression model analysis, F test, and t test. The results of this study are compatibility and perceived content have a significant effect to intention to switch. Only convenience is has no effect to intention to switch. Keywords : new product attributes; intention to switch; electronic money